The Impact of the Quality of Accounting Information Systems and Non-Financial Information on the Performance of Small and Medium Enterprises (SMEs) in Bengkulu - Elsyavera Arystin; sriwidharmanely, sriwidharmanely; Nila Aprilla (Jurnal Akuntansi, 2025)
This study aims to analyze the influence of the Quality of Accounting Information Systems (KSIA) and Non-Financial Information (INK) on Financial Performance (KK) and Non-Financial Performance (KNK) in Small and Medium Enterprises (SMEs) in Bengkulu Province. The research approach used quantitative methods with the help of WarpPLS 7.0 software, and data was obtained from 45 SMEs that have implemented accounting information systems in their operational activities. The results of the study show that the quality of accounting information systems has a positive and significant effect on the financial and non-financial performance of SMEs. Non-financial information has a significant positive effect on the financial performance of SMEs, but the effect on non-financial performance is positive but not significant. Non-financial performance does not have a significant effect on the financial performance of SMEs. These findings affirm the importance of improving the quality of accounting information systems and the use of non-financial information to support the sustainable performance of SMEs.